PENGUATAN METODE PENGAJARAN BAGI KELEMBAGAAN TAMAN PENDIDIKAN ALQURAN (TPQ) AL-CHUSNA DESA BUTUH KECAMATAN TEGALREJO KABUPATEN MAGELANG - Ahmad Prayoga; Ahmad Saifudin (khidmatan, 2021)
Alquran Learning Center (TPQ) is an institution or community group that organizes informal education of the Islamic religion to teach reading the Qur'an from an early age. The purpose of TPQ is to provide basic provisions for students to be able to read the Qur'an correctly and precisely according to the science of recitation and also to instill Islamic values for students. The community really hopes and immediately asks the student study service to fix the TPQ teaching method, because they do not have standardization and good and effective teaching methods in the application of their daily activities. The purpose of this community service is to improve the TPQ teaching method that is more effective. In this study, the author uses the Asset Based Community Development (ABCD) method where the author tries to strengthen teaching methods at institutions in reducing the ineffectiveness of learning during this pandemic. During the mentoring process that the Service Team carried out, there was an increase in learning methods and children's interest in participating in learning at the TPQ Al-Chusna Butuh village